CJEU: Germany's Public Prosecution Authorities Cannot be Regarded as a "Judicial Authority" with Regard to EAWs-The Truth or a Misconstrual of the Legal Reality? - Glaser, Sebastian; Hartmann, Sarah (German Law Journal, 2022)
The judgment rendered by the Court of Justice of the European Union (CJEU) on May 27, 2019, deemed Germany's prosecution service (Staatsanwaltschaft) legally incompetent for the purpose of issuing European arrest warrants (EAW) due to its lack of institutional independence. As a consequence, the question of how the German criminal prosecution system differs from the approaches taken by other European countries issuing European arrest warrants arises and raises the question of whether the German prosecution service truly is insufficiently independent in this respect. Debates amongst legal scholars have ensued in the wake of the CJEU's judgment-the Court not yet having proffered any solutions regarding the re-establishment of the institutional independence-and this article shall discuss the lack of independence and acquaint the reader with possible solutions.
CRIS-Team WoS Importer:2022-07-01
Keywords: Public prosecutor’s office; staatsanwaltschaft; public prosecution authorities; issuing judicial authority; European Court of Justice; EAW; European Arrest Warrant